OC-090 Different effects of FODMAP (fermentable oligo-, di-, and mono-saccharides, and polyols) components on small bowel water content: an MRI study. (28th May 2012) - Murray, K; Wilkinson-Smith, V; Lam, C; Hoad, C; Cox, E; Costigan, C; Marciani, L; Gowland, P; Spiller, R
Abstract : Introduction: A randomised placebo controlled trial (RCT) has shown that FODMAPs exacerbate irritable bowel syndrome (IBS) symptoms in selected patients. FODMAPs are heterogeneous chemically, the major components being fructose and fructans. Both are poorly absorbed in the small bowel but fructose exerts a much greater osmotic effect than fructans which are fructose polymers. Whether this alters the overall impact is unknown. This study aims to test the hypotheses that (a) fructose will increase small bowel water content (SBWC) more than fructans; (b) adding glucose to fructose will reduce its effect, and (c) fructans will exert most of their effect as a result of colonic fermentation. Methods: 4-way, randomised, single blind, crossover study. 16 healthy volunteers underwent abdominal scans in a 1.5T MRI scanner after an overnight fast. They were then fed 500 ml of water containing 40 g glucose, fructose, fructan or 40 g glucose plus 40 g fructose and underwent scanning and breath H2 measurement and completed bowel symptom questionnaires at hourly intervals for 5 h. SBWC was measured from heavily T2 weighted magnetic resonance scans. 1-way analysis of variance was used. Results: (Mean±SEM) All drinks were well tolerated with only minor symptoms of gas, bloating, abdominal pain and diarrhoea reported. Relative to glucose, fructose increased SBWC significantly (184±35 ml vs 118±24 ml glucose, p=0.001), while fructans had little effect (SBWC=119±23 ml, p=0.7 vs glucose). Adding 40 g glucose to 40 g fructose decreased SBWC (145±27 ml, but the difference was not significant, p=0.08 vs fructose). Breath H2 was initially higher for fructose than the other three solutions. (AUC was 8959±1880 ppm.min) with fructans having the largest AUC at 14 987±2568 ppm.min). Values returned to baseline for fructose over the 5 h study, but increased to a maximum for fructan after 300 min. Glucose had no effect on breath H2 concentration, but adding an equivalent amount to fructose significantly reduced breath H2 relative to fructose alone (p=0.0006). Conclusion: FODMAPs exert a variety of GI responses. Fructose but not fructans increases SBWC relative to glucose. Both fructose and fructans are malabsorbed as confirmed by breath H2 measurements. Fructose malabsorption is significantly reduced by addition of glucose. These different gastrointestinal responses can be readily identified using our non-invasive MRI techniques. Competing interests: None declared.